Efektivitas Media Daring Pembelajaran PAI Siswa Kelas VIII Di SMP Pahlawan Toha Kota Bandung - Mochamad Fadlani Salam; Siti Halimah Syadiah (LPPAIK Universitas Muhammadiyah Bandung, 2022)
The decrease in the enthusiasm for learning in students shows that students are still less motivated to explore PAI subjects. This habit is because students are not used to using technology as a learning medium. The purpose of this study was to determine the effectiveness of PAI learning in using online media in class VIII students at Pahlawan Toha Junior High School, Bandung City. This study uses a qualitative approach with phenomenological methods. The technique in this study uses triangulation, namely, interviews, observation and documentation. The results showed that the effectiveness of PAI learning using online media was quite effective. It is evident from the achievement of indicators of learning effectiveness with a very high percentage of 77.3%, it can be concluded that PAI learning using online media for class VIII students at SMP Pahlawan Toha City Bandung is effective.